The Harmonious Dialectics Between Hindu-Muslim in Bali (A Study in Jembrana Regency) - Saihu, Made; Sahin, Cemal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper discusses the harmonious dialectics process between Hindus and Muslims through ‘urf or localwisdom which is believed to have philosophical, sociological, and psychological values with pluralmulticultural nuances for the community of Jembrana, Province of Bali. This paper focuses on searching theeffectiveness of some ‘urf or local wisdom that functioning as a means of interacting between two religiouscommunities leading to peaceful practices on Hindu-Muslim communities in Jembrana-Bali. The datasources are field observations and unstructured interviews from March-July 2019. This study is a fieldresearch using a case study method. The results show that the dialectics process with a multicultural nuancebetween Hindus and Muslims in Jembrana is through the ‘urf or local wisdom, namely male, ngejot,rebana, and mekepung traditions. Furthermore, from these four traditions, there is a process of activeinvolvement, constructive understanding, and efforts to find joint commitments from various commitments sothat a sense of brotherhood and understanding of the diversity between the two religious communities becomesextremely close. This dialectic can also shape the character of Hindu and Muslim communities in Jembranato be humanist, tolerant, and inclusive, this phenomenon then leads to the process of association, integration,complementation, and sublimation. This research contributes to the field of religious and cultural studies bydemonstrating how ‘urf traditions serve as mechanisms for fostering tolerance, humanism, and inclusivity ina pluralistic society. It confirms the theory that Islamization in the region is not a confrontational processbut rather an adaptive and integrative one. Methodologically, this study highlights the significance ofqualitative case studies in exploring interfaith relations through localized traditions.